Energy loss analysis of the double-suction centrifugal pump under different flow rates based on entropy production theory. (October 2020) - Guan, Hongyu; Jiang, Wei; Yang, Jianguo; Wang, Yuchuan; Zhao, Xinghai; Wang, Junxue
The investigation of energy loss of pump is of great significance for energy conservation and structural optimization design. And traditional methods have great limitations in researching the distribution of energy losses. In this paper, the entropy production theory is utilized to analyze the energy loss of the double-suction centrifugal pump. The numerical simulation results verified by experiments indicate that the difference in total entropy production under different flow rates is mainly affected by the entropy production in the main flow region. Moreover, the entropy production of the volute has the greatest impact on the entropy production in the main flow region, and even the proportion of entropy production in the volute at 1.2 QD operating point reaches 96%. Besides, the Q-criterion is applied to study the morphology of the vortex core in the volute. In the volute inlet region, it is found that the stable double-vortex flow has a better flow field and less energy loss than the scattered wake vortex.